PENDIDIKAN KESEHATAN CUCI TANGAN SEBAGAI UPAYA PENERAPAN BUDAYA PERILAKU HIDUP BERSIH SEHAT MASA ENDEMI PADA SISWA- SISWI DI SEKOLAH MENENGAH PERTAMA NEGERI 12 MAKASSAR - sriwahyuni; Sri Darmawan (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2024)
At the beginning of 2020, Indonesia and even the world were shocked by the Coronavirus Disease 2019 (Covid-19) outbreak with the number of positive infections amounting to 71,051,805 people with 1,608,648 deaths, Coronavirus Disease 2019 (Covid-19) can spreads quickly through the nose and mouth, physical contact such as shaking hands so washing hands with soap is very important to minimize Coronavirus Disease 2019 (Covid-19). This activity was held on January 18-19 2023 at Makassar Middle School 12 which had 702 students consisting of classes VII to IX but the participants in this activity were 32 class VII.1 students. students. The methods used are pre and post tests through questioners and providing material as well as direct observation when students wash their hands, which aims to determine the level of knowledge of students regarding the implementation of the culture of clean and healthy living behavior (PHBS) during the endemic period. Based on the results of the pre-test and post-test as well as observations, data showed that there was an increase in knowledge, where before being given health education, only 29 (90.6%) students had good knowledge and 3 (9.4%) had poor knowledge. students, but after being given health education, the students' knowledge increased to 32 (100%) who had good knowledge, so it can be concluded that there is an influence of health education on hand washing on the implementation of a culture of clean and healthy living behavior (PHBS) during the endemic period in State Junior High Schools. 12 Makassar.